2016
DOI: 10.3390/su8090940
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Mitigation of Nutrient Pollution and Overland Water Flow Change on the Florida Everglades, USA

Abstract: Abstract:A subtropical watershed and wetland covering nearly 47,000 km 2 in the southeastern United States, the Florida Everglades is a degraded, human-dominated environment. As a unique and important ecosystem, the Everglades provide a variety of important environmental services for society and nature. Over the past century and a half, anthropogenic actions have severely impacted the Everglades by disrupting the natural water flow and causing water pollution. As a result, the native flora and fauna have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Consequently, TN and TC contents were also highest in midway (M) soil samples. In unimpacted Everglades soils (those not influenced by allochthonous sources of P), TP is often correlated with TC [19]; however, this was not the case in our analysis, indicating the possibility of an influence of external P loading (causing a biogeochemical disconnect) from agricultural areas [20]. Table 1.…”
Section: Resultsmentioning
confidence: 54%
“…Consequently, TN and TC contents were also highest in midway (M) soil samples. In unimpacted Everglades soils (those not influenced by allochthonous sources of P), TP is often correlated with TC [19]; however, this was not the case in our analysis, indicating the possibility of an influence of external P loading (causing a biogeochemical disconnect) from agricultural areas [20]. Table 1.…”
Section: Resultsmentioning
confidence: 54%
“…This can be seen as an increase in total P content in the biochar for both BC P and Fe‐BC P by 16% to 110% from its native state and the diminished plant available P shown in the formic acid extractions of recovered biochar. Slow release of P in fertilizers and soil amendments can help address the issue of phosphorus runoff from agricultural fields that can contribute to HABs (Hallegraeff et al, 2004; Schade‐Poole & Möller, 2016). The study also showed that adding ferric iron to the biochar increased its sorption capacity.…”
Section: Discussionmentioning
confidence: 99%
“…A month‐long study was conducted to treat P in the SLW using (1) iron‐only reactive filtration (HFO‐RF or Fe‐RF) and (2) iron and biochar (Fe‐BC‐RF) process configurations. For each process configuration, two target TP influent concentrations were set (0.075 and 0.22 mg/L), and these were chosen to mimic typical TP concentrations of Lake Okeechobee in Florida, USA, a 1900‐km 2 phosphorus‐polluted, HAB‐impacted lake (Schade‐Poole & Möller, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Eutrophication from phosphorus (P) pollution remains among the most serious challenges of Everglades restoration (Schade‐Poole & Möller 2016). Naturally low levels of nutrients in the Everglades form a unique, oligotrophic ecosystem of specific flora and fauna (Brix et al 2010).…”
Section: Introductionmentioning
confidence: 99%